Sequels of COVID-19 and the role of health professionals - Porras Vásquez, Tonia Paola (2023)
Objective: Describe the main sequelae of COVID-19 and the role of health professionals. Method: A bibliographic review based on health descriptors from various databases was carried out. Some articles were selected and analyzed according to the general categories of signs, symptoms and sequelae. Main results: The main organic-systemic sequelae are: neurological, respiratory, cardiovascular, musculoskeletal and psychiatric/psychological. On the other hand, health professionals are required to provide comprehensive care to the patient, being humane professionals and sensitive to the multi-organ disorders of people with persistent COVID-19. Overall conclusion: Given the importance of interaction with people affected by persistent COVID-19, collaboration and coordination between health professionals in the area of ​​medicine, nursing, psychology and physical therapy is essential for effective treatment.